2021
DOI: 10.1093/scan/nsab037
|View full text |Cite|
|
Sign up to set email alerts
|

The posterior cerebellum and inconsistent trait implications when learning the sequence of actions

Abstract: It has been proposed that the cerebellum contributes to social cognition. Based on the view that cerebellar internal models create predictions on motions and actions, we hypothesize that the posterior cerebellum supports identifying temporal sequences of persons’ actions as well as detecting inconsistent actions that violate the implied trait. Participants were required to memorize the temporal order of a set of sentences that implied a personality trait. Importantly, the sentence sets were designed in such a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 36 publications
(68 reference statements)
4
23
1
Order By: Relevance
“…Another recent meta-analysis found that a great majority (74%) of approximately 200 studies with activation in the posterior cerebellar Crus II revealed task processes involving mentalizing or self-related emotion attribution (Van Overwalle, Ma, & Heleven, 2020a). Recent fMRI studies further indicated that the posterior cerebellum was highly activated when social tasks required the generation of social action sequences, such as giving the correct chorological order of stories involving beliefs (Heleven et al, 2019), memorizing the order of actions implying traits of other people (Pu et al, 2020;Pu et al, 2021), or predicting sequential actions of persons based on their traits (Haihambo et al, 2021). Together, these studies suggest that the posterior cerebellum, especially Crus I and II, plays a critical role in identifying the sequence of social actions while inferring the mental state of other persons and may aid in anticipating and inferring others' mental states during dynamic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent meta-analysis found that a great majority (74%) of approximately 200 studies with activation in the posterior cerebellar Crus II revealed task processes involving mentalizing or self-related emotion attribution (Van Overwalle, Ma, & Heleven, 2020a). Recent fMRI studies further indicated that the posterior cerebellum was highly activated when social tasks required the generation of social action sequences, such as giving the correct chorological order of stories involving beliefs (Heleven et al, 2019), memorizing the order of actions implying traits of other people (Pu et al, 2020;Pu et al, 2021), or predicting sequential actions of persons based on their traits (Haihambo et al, 2021). Together, these studies suggest that the posterior cerebellum, especially Crus I and II, plays a critical role in identifying the sequence of social actions while inferring the mental state of other persons and may aid in anticipating and inferring others' mental states during dynamic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…• In one study, we explored to what extent the posterior cerebellar Crus might be sensitive to deviations from previously acquired knowledge, not only in sequences, but also in higher level social information caused by inconsistencies revealed by social mentalizing, such as inconsistencies in trait implications revealed by inconsistent actions in a person's actions. To investigate this, Pu et al [42] slightly modified the previous study by Pu et al [37]. As in that study, participants were required to memorize the given temporal order of a series of social actions of a protagonist that implied a personality trait.…”
Section: Beyond Action Sequencing: Social Inconsistencies and Sequenc...mentioning
confidence: 99%
“…C Implicit belief serial response time [36]. D Trait-inconsistent action sequences [42]. E Trait-based action prediction [43] • Besides observing actions of others here and now, we also tested the hypothesis that the cerebellum might be a coprocessor in the service of predictive coding [23] supporting the prediction of future actions.…”
Section: Beyond Action Sequencing: Social Inconsistencies and Sequenc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, understanding the direct role of the cerebellum in ToM remains challenging. A handful of imaging studies with healthy participants demonstrated cerebellar activation when performing a mentalizing task 17 21 . Yet, only a small portion of the studies reported cerebellar activation during social judgments, including mentalizing 13 , 22 .…”
Section: Introductionmentioning
confidence: 99%